2021
DOI: 10.1108/dta-04-2021-0088
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing online discussion data for understanding the student's critical thinking

Abstract: PurposeCritical thinking is considered important in psychological science because it enables students to make effective decisions and optimizes their performance. Aiming at the challenges and issues of understanding the student's critical thinking, the objective of this study is to analyze online discussion data through an advanced multi-feature fusion modeling (MFFM) approach for automatically and accurately understanding the student's critical thinking levels.Design/methodology/approachAn advanced MFFM appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…LIWC 2015 “all fields” search key criteria indicates 54 studies, 16 of which with specific focus on LIWC-2015. From these, 7 are of interest for health and education ( Stanton et al, 2017 ; Chippendale and Gentile, 2021 ; Monzani et al, 2021 ; Ansari and Du, 2022 ; Yang et al, 2022 ; Sengun et al, 2023 ; Wu et al, 2023 ). Moreover, 7 studies ( Toma and D’Angelo, 2015 ; Coello-Guilarte et al, 2019 ; Kimball et al, 2019 ; Berkout et al, 2020 ; McDonnell et al, 2020 ; Dudău and Sava, 2022 ; Meyerhoff et al, 2023 ) focus on the use of LIWC in connection with depression, all of them relevant for the topic of this study.…”
Section: Methodsmentioning
confidence: 99%
“…LIWC 2015 “all fields” search key criteria indicates 54 studies, 16 of which with specific focus on LIWC-2015. From these, 7 are of interest for health and education ( Stanton et al, 2017 ; Chippendale and Gentile, 2021 ; Monzani et al, 2021 ; Ansari and Du, 2022 ; Yang et al, 2022 ; Sengun et al, 2023 ; Wu et al, 2023 ). Moreover, 7 studies ( Toma and D’Angelo, 2015 ; Coello-Guilarte et al, 2019 ; Kimball et al, 2019 ; Berkout et al, 2020 ; McDonnell et al, 2020 ; Dudău and Sava, 2022 ; Meyerhoff et al, 2023 ) focus on the use of LIWC in connection with depression, all of them relevant for the topic of this study.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike CNN, RNN imitates human reading behavior by extracting semantic representations from left to right of the entire review text. However, as RNN are not ideal for capturing long-distance semantic connections and face vanishing gradient problems (Yang et al , 2022), their variation, known as long short-term memory (LSTM), is more commonly applied. For example, Luo and Xu (2021) applied LSTM to predict the sentiments of online restaurant reviews and demonstrated that the DL technique has a better ability to perform prediction tasks.…”
Section: Literature Review and Research Backgroundmentioning
confidence: 99%
“…Discussion is an excellent technique to learn and build conceptual understanding because it involves an exchange of viewpoints that students can consider and reject or embrace (Zarifsanaiey et al, 2016;Bean & Melzer, 2021;Shuhong, 2023). In addition, through discussion, students can reduce disagreements between themselves and other students (Kager et al, 2022;Yang et al, 2022). Due to the integration between these learning models by considering the cultural and ecological environment along with the community values contained in the Engklek game to produce a science-literate generation with innovative skills and scientific attitudes (Sudarmin, 2014).…”
Section: Very Large 070 Largementioning
confidence: 99%